The Germanies (revolts of the Brotherhoods) in the kingdoms of Valencia and Mallorca - Pablo Pérez García (Catalan Historical Review)
This article offers a comparative analysis of the brotherhoods (germanies1) and their respective revolts (also called Germanies) in Valencia and Mallorca from the historical, historiographic and memorialist vantage points. The most salient aspects of both movements within the historical context of the early 1520s are highlighted.